Principles of ‘Newspeak’ in Polish Translations of British and American Press Articles under Communist Rule - Źrałka, Edyta (Research in Language, 2017)
The paper analyses selected Polish translations of British and American press articles published in the magazine Forum in the years 1965 – 1989. In communist Poland, all such texts were censored before publication, which forced the translators to avoid content and language that could be banned by censors and to adopt a specific style of expression known as Newspeak. The paper lists the linguistic phenomena in the target language that represent features typical of Newspeak and identifies manipulative procedures which led to their occurrence, using a corpus of 25 English texts and their Polish translations.